2022
DOI: 10.1002/sstr.202100194
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Shell Passivation in Ln3+‐Doped Luminescent Nanocrystals

Abstract: d) Morphology evolution of β-NaYF 4 :Yb 3þ , Er 3þ @β-NaLuF 4 :Nd 3þ nanocrystal as rising Nd 3þ concentration in the shell; e) the corresponding emission spectra upon 800 nm excitation; and f ) the variation of the Er 3þ luminescence intensity arising from different excited states. Adapted with permission. [39]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 196 publications
2
17
0
Order By: Relevance
“…That is to say, there is a vast gap between theoretical interpretation and experimental investigation of phonon mediation in Ln 3+ -doped nanocrystals, and it is still unclear whether it is rational to explore the nature of a microscopic phenomenon occurring at the nanoscale based on experimental results obtained by a macroscopic measurement without necessary standardization and correction. 50 In addition, recent research has revealed that a clear awareness of the structural details of nanomaterials 225 and the degree of chemical disorder 26 are crucial to interpreting the optical properties of Ln 3+ -doped nanocrystals. Systematical studies are needed in the future to clarify these issues, which will be mandatory for the informed development of Ln 3+ -doped luminescent nanomaterials that can meet the application needs for a sustainable society.…”
Section: ■ Phonon Mediation At the Nanoscalementioning
confidence: 99%
See 1 more Smart Citation
“…That is to say, there is a vast gap between theoretical interpretation and experimental investigation of phonon mediation in Ln 3+ -doped nanocrystals, and it is still unclear whether it is rational to explore the nature of a microscopic phenomenon occurring at the nanoscale based on experimental results obtained by a macroscopic measurement without necessary standardization and correction. 50 In addition, recent research has revealed that a clear awareness of the structural details of nanomaterials 225 and the degree of chemical disorder 26 are crucial to interpreting the optical properties of Ln 3+ -doped nanocrystals. Systematical studies are needed in the future to clarify these issues, which will be mandatory for the informed development of Ln 3+ -doped luminescent nanomaterials that can meet the application needs for a sustainable society.…”
Section: ■ Phonon Mediation At the Nanoscalementioning
confidence: 99%
“…As a typical example for this, the UCL quantum yield (QY) of small-sized Yb 3+ , Er 3+ -doped hexagonal-phase NaYF 4 (abbreviated as β-NaYF 4 ) nanocrystals is reported to be less than 1% upon 980 nm laser excitation with a moderate power density, which is in stark contrast to the 10% of the bulk counterpart . Taking into consideration the large surface-to-volume ratio (SVR) of nanocrystals, it is viewed that the emergence of energy dissipation processes on the surface of nanocrystals is primarily responsible for the difference of several orders of magnitude in QY between bulk and nanocrystal. Yet, it also has to be recognized that even for Ln 3+ -doped β-NaYF 4 bulk crystals, the observed luminescence QY is significantly less than the near-unity QY of commercially used Ln-doped luminescent materials, such as 87% for Y 3 Al 5 O 12 :Ce 3+ and 96% for β-SiAlON:Eu 2+ . The validity of this direct numerical comparison is, however, questionable because of the different luminescence mechanisms in the various materials. ,, Particularly, the effect brought about by the nonlinearity of the upconversion process should be considered .…”
mentioning
confidence: 99%
“…The emission spectra of 2 and 3 measured at the lowest measured P D display analogous emission spectra of 1, except for the worse SNR (Supplementary Figure S1). As the shell gets thicker, the luminescence quenching effects are reduced (Pini et al, 2022;Shi et al, 2022) leading to higher SNR and advantageously decreased temperature uncertainty. As initially proposed by some of us (Brites et al, 2016), and experimentally implemented by others (Van Swieten et al, 2021), the temperature uncertainty increases as the SNR degrades.…”
Section: Primary Thermometermentioning
confidence: 99%
“…[32,77,[108][109][110][111][112][113][114][115] Meanwhile, core-shell nanostructures are increasingly used to increase the quantum yield but the structural integrity still needs deep understanding. [116][117][118][119][120][121] Furthermore, some fundamental questions are receiving systematic investigation, for example, how dopants diffusion with stimuli, under which circumstances the carriers are really free versus localized, which are meaningful for potential applications. [122,123] In view of this blank, we systematically discuss the recent achievements to directly image the microstructure and local environment of activators (Ln and Mn 2+ ) in luminescent materials with advanced electron microscopy techniques as shown in Table 2, including: 1) bulk materials, the typical systems are nitride/oxynitride phosphors; and 2) nanomaterials, such as nanocrystals (hexagonal-phase NaLnF 4 and perovskite) High defect tolerance, excellent brightness, tunable emission wavelength with higher efficiency, high color purity, and the stability is poor.…”
Section: Introductionmentioning
confidence: 99%